A survey of vascular specialists' practice patterns of inferior vena cava filter placement and retrieval. (June 2019) - Brahmandam, Anand; Skrip, Laura; Sumpio, Bauer; Indes, Jeffrey; Dardik, Alan; Sarac, Timur; Rectenwald, John; Chaar, Cassius Iyad Ochoa
Objectives: The placement of inferior vena cava filters (IVCF) continues to rise. Vascular specialists adopt different practices based on local expertise. This study was performed to assess the attitudes of vascular specialists towards the placement and retrieval of IVCF. Methods: An online survey of 28 questions related to practice patterns regarding IVCF was administered to 1429 vascular specialists. Vascular specialists were categorized as low volume if they place less than three IVCF per month and high volume if they place at least three IVCF per month. The responses of high volume and low volume were compared using two-sample t-tests and Chi-square tests. Results: A total of 259 vascular specialists completed the survey (18% response rate). There were 191 vascular surgeons (74%) and 68 interventional radiologists (26%). The majority of responders were in academic practice (67%) and worked in tertiary care centers (73%). The retrievable IVCF of choice was Celect (27%) followed by Denali (20%). Forty-two percent used a temporary IVCF and left it in situ instead of using a permanent IVCF. Eighty-two percent preferred placing the tip of the IVCF at or just below the lowest renal vein. Thirty-one percent obtained a venous duplex of the lower extremities prior to retrieval while 24% did not do any imaging. There were 132 (51%) low volume vascular specialists and 127 (49%) high volume vascular specialists. Compared to low volume vascular specialists, significantly more high volume vascular specialists reported procedural times of less than 30 min for IVCF retrieval (57% vs. 42%, P = 0.026). There was a trend for high volume to have fewer unsuccessful attempts at IVCF retrieval but that did not reach statistical significance ( P = .061). High volume were more likely to have attempted multiple times to retrieve an IVCF (66% vs. 33%, P < .001), and to have used bronchoscopy forceps (32% vs. 14%, P = .001) or a laser sheath (14% vs. 2%, P < .001) for IVCF retrieval. In general, vascular specialists were not comfortable using bronchoscopy forceps (65%) or a laser sheath (82%) for IVCF retrieval. Conclusions: This study underscores significant variability in vascular specialists practice patterns regarding IVCF. More studies and societal guidelines are needed to define best practices.